Organizing The Subject of Atomic Structure, Ruserford and Frank-Gers Experience on The Basis of New Pedagogical Technologies - Qurbonaliyev Qobiljon Qosimjon o’g’li; Parpiboyeva Nilufarxon Zoxidjon qizi; Odiljonova Zarifaxon Zoirjon qizi; Sobirova Gulnoza Zoirjon qizi (Euro Asian Journal Publishing, 2023)
This article talks about introducing information about the initial ideas about the structure of the atom, the thought of Democritus, the Thomson model of the atom, the experiments of Rutherford and Frank-Gers, the planetary model of the atomic nucleus of Rutherford, and teaching them based on modern pedagogical technologies.
Keywords: Atom; Democritus; Thomson; Rutherford